Determinan Profitabilitas Industri Perbankan yang Terdaftar di Bursa Efek Indonesia - Liza Rahmayani; Dahlia Tri Anggraini (Jurnal Akuntansi dan Governance, 2021)
This research aims to find out the determinants of profitability in banking companies. This research is quantitative with the population of banking companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019, and used purposive sampling techniques that obtained samples of 27 banking companies. Data analysis techniques in this research is descriptive statistical analysis and panel data regression. This study obtained the results that BI rate, inflation, and Non Performing Loan (NPL) simultaneously have a significant effect on profitability. While partially, BI rate and inflation have insignificant negative effect on profitability, and NPL has a significant negative effect on profitability.